The Impact of Methylphenidate on Pubertal Maturation and Bone Age in ADHD Children and Adolescents: Results from the ADHD Drugs Use Chronic Effects (ADDUCE) Project - Carucci, Sara; Zuddas, Alessandro; Lampis, Angelico; Man, Kenneth K. C.; Balia, Carla; Buitelaar, Jan; Danckaerts, Marina; Dittmann, Ralf; Donno, Federica; Falissard, Bruno; Gagliano, Antonella; Garas, Peter; et al. (Journal of attention disorders, 2024)
Objective: The short-term safety of methylphenidate (MPH) has been widely demonstrated; however the long-term safety is less clear. The aim of this study was to investigate the safety of MPH in relation to pubertal maturation and to explore the monitoring of bone age. - Method: Participants from ADDUCE, a two-year observational longitudinal study with three parallel cohorts (MPH group, no-MPH group, and a non-ADHD control group), were compared with respect to Tanner staging. An Italian subsample of medicated-ADHD was further assessed by the monitoring of bone age. - Results: The medicated and unmedicated ADHD groups did not differ in Tanner stages indicating no higher risk of sexual maturational delay in the MPH-treated patients. The medicated subsample monitored for bone age showed a slight acceleration of the bone maturation after 24 months, however their predicted adult height remained stable. - Conclusion: Our results do not suggest safety concerns on long-term treatment with MPH in relation to pubertal maturation and growth.
Gesehen am 09.01.2025